Synchronous Ipsilateral Adrenal and Retroperitoneal Ganglioneuroma: A Unique Case of Large Tumor Mass - Abdolreza Mohammadi; Fardin Asgari; Ehsan Zemanati Yar; Mina Rezayat; Mahdi Najarzadegan; Seyed Mohammad Kazem Aghamir (Case Reports in Medicine)
This case report presents a rare instance of synchronous adrenal ganglioneuroma and an ipsilateral retroperitoneal mass in a 51-year-old woman with episodic hypertensive crises and increased symptom frequency. Imaging revealed a hypodense mass near the right kidney and an additional adrenal mass, which led to surgical intervention. Laboratory findings indicated hypercortisolism, and both masses were surgically removed by the laparoscopy approach. Postoperative pathology identified both masses as maturing-type ganglioneuroma, with no signs of malignancy or complications. This case highlights the diagnostic and therapeutic challenges of such rare presentations and emphasizes the importance of detailed imaging, surgical excision, and histopathological analysis. The potential link between elevated cortisol levels and ganglioneuroma, as observed here, underscores the need for further research into these benign tumors.